2022
DOI: 10.1038/s41598-022-08809-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prepartum dietary energy density on beef cow energy metabolites, and birth weight and antioxidative capabilities of neonatal calves

Abstract: The objective of this study was to investigate the effect of prepartum diets that differ in energy density on beef cow energy metabolites and birth weight, immunity and antioxidative capabilities of neonatal calves. On d 0 (approximately 45 d before calving), 90 multiparous Angus cows (BW = 510 ± 16 kg) were randomly allocated into 1 of 9 drylot pens (10 cows/pen). Each pen was randomly assigned to a treatment condition (three pens/treatment), the cows in each treatment were assigned randomly to receive a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…In the current study, higher dietary energy density of beef cows increased the birth weight of calves, suggesting that the fetus could obtain more nutrients from the cows, which was conducive to promoting growth. A recent study reported that calves born to cows fed the high energy ration during gestation were significantly heavier than those born to cows fed low energy ration at birth (28), which were in accordance with our results.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current study, higher dietary energy density of beef cows increased the birth weight of calves, suggesting that the fetus could obtain more nutrients from the cows, which was conducive to promoting growth. A recent study reported that calves born to cows fed the high energy ration during gestation were significantly heavier than those born to cows fed low energy ration at birth (28), which were in accordance with our results.…”
Section: Discussionsupporting
confidence: 93%
“…Maternal energy level affected the antioxidant ability of neonatal calves. A previous study found that higher maternal dietary energy could enhance the activity of serum GSH-Px, SOD and T-AOC in neonatal calves ( 28 ). However, in our study, the serum GSH-Px and T-AOC activities of neonatal calves in HE group were lower than LE group.…”
Section: Discussionmentioning
confidence: 98%
“…In the figure, the different colors represent the differential metabolites in different comparison groups, the overlapping part represents the number of metabolites common to multiple metabolic sets, and the bar graph represents the number of metabolites included in each metabolic set. (Chen et al, 2022). The study showed that yaks in the MG group had faster monthly growth compared to the LG group, as energy levels increased, yaks in the HG group gained more weight, with a higher average daily gain than the other two groups.…”
Section: Discussionmentioning
confidence: 89%
“…Consequently, there is a pressing need for a change in feeding patterns to promote animal husbandry in the QTP ( Long et al, 1999 ; Xue et al, 2005 ). Prior research indicates that pre-partum heifers body weight and performance can be enhanced by varying their dietary energy levels ( Chen et al, 2022 ). The study showed that yaks in the MG group had faster monthly growth compared to the LG group, as energy levels increased, yaks in the HG group gained more weight, with a higher average daily gain than the other two groups.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate that the energy supplied from the M and L diets plus the body fat mobilization in the jennets could meet the energy demand for fetal growth, even at the lower level of dietary energy supplied in the present study. Studies in beef cattle have shown the importance of pre-partum dietary energy levels for neonatal calves on calf birth weight ( Chen et al, 2022 ) with only severe maternal energy deficiency impairing the birth weight of the offspring. This was not the case in this donkey study.…”
Section: Discussionmentioning
confidence: 99%